2022
DOI: 10.1371/journal.pgph.0001126
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of the number and distribution of zero-dose and under-immunised children across remote-rural, urban, and conflict-affected settings in low and middle-income countries

Abstract: While there has been great success in increasing the coverage of new childhood vaccines globally, expanding routine immunization to reliably reach all children and communities has proven more challenging in many low- and middle-income countries. Achieving this requires vaccination strategies and interventions that identify and target those unvaccinated, guided by the most current and detailed data regarding their size and spatial distribution. Through the integration and harmonisation of a range of geospatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…Still, many proposals did mention having large pockets of unimmunised children in large urban areas and slums. It is estimated that 28% of un- or under-vaccinated children lived in urban and peri-urban areas and up to 15% lived in conflict-affected areas in 2020 [ 24 ]. It would thus be beneficial to pay special attention to those populations.…”
Section: Discussionmentioning
confidence: 99%
“…Still, many proposals did mention having large pockets of unimmunised children in large urban areas and slums. It is estimated that 28% of un- or under-vaccinated children lived in urban and peri-urban areas and up to 15% lived in conflict-affected areas in 2020 [ 24 ]. It would thus be beneficial to pay special attention to those populations.…”
Section: Discussionmentioning
confidence: 99%
“…The ongoing COVID-19 pandemic has contributed to at least some of today’s gaps in childhood vaccination [ 3 ], with estimates of under-one children without any doses of the diphtheria–tetanus–pertussis vaccine (no-DTP) rising from 10% prevalence in 2019 to 14% in 2021 [ 3 ]. Communities with high levels of unvaccinated or “zero-dose children” often face myriad vulnerabilities [ 4 , 5 , 6 , 7 ], such as residing in highly remote areas or informal settlements in cities [ 7 , 8 , 9 ]; being affected by displacement and/or prolonged conflict or unrest [ 7 , 8 ]; longstanding poverty and/or societal neglect [ 4 ]; or some constellation of these factors. Subsequently, optimally identifying where and how to better reach zero-dose children will likely require a combination of context-specific strategies and broader investments to address persisting structural challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years, a growing body of research has sought to assess characteristics of zero-dose children and their families or households, as well as potential drivers of high zero-dose prevalence at different geographic levels [ 4 , 5 , 6 , 7 , 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Past work has found that zero-dose children experience a higher odds of missing or lacking access to other types of primary care services [ 6 , 11 , 12 ], while their mothers were more likely to have no antenatal care visits and not deliver at a health facility [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, zero-dose children are more likely to have limited access to water, sanitation, and education [12] and live in poorer households [11]. A substantial number of zero-dose children also live in proximity to conflict [13]. Therefore, more deliberate provisioning of multiple interventions or services in contact with health systems or providers, including vaccination services, could be an efficient way to reach at-risk children and communities and reduce health inequalities.…”
Section: Introductionmentioning
confidence: 99%
“…At the population level, analyses of the spatial overlap between gaps in immunization coverage and other health services can complement these individual-level analyses. Spatial analyses conducted in recent years have emphasized the substantial degree of subnational inequality in vaccine coverage [13,[17][18][19][20][21][22][23], as well as other key health services and indicators [22,[24][25][26][27][28][29][30][31]. Fewer studies have assessed whether subnational distributions of zero-dose (or no-DTP) children are similar to those for other health indicators [32].…”
Section: Introductionmentioning
confidence: 99%